Hybridizing semiconductor nanocrystals with metal–organic frameworks for visible and near-infrared photon upconversion. Issue 26 (15th March 2018) - Amemori, Shogo; Gupta, Rakesh Kumar; Böhm, Marcus Leo; Xiao, James; Huynh, Uyen; Oyama, Tomoki; Kaneko, Kenji; Rao, Akshay; Yanai, Nobuhiro; Kimizuka, Nobuo
Abstract : Solid upconverters consisting of semiconductor nanocrystals and metal–organic frameworks (MOFs) show NIR-to-visible TTA-UC with large anti-stokes shifts. Abstract : Hybrid materials consisting of semiconductor nanocrystals and metal–organic frameworks (MOFs) were prepared for the first time to achieve photon upconversion based on triplet–triplet annihilation (TTA-UC) in the solid-state, which allowed TTA-UC with large anti-Stokes shifts in the visible and near-infrared regions.